DIALOGICAL SPEECH IN UZBEK AND ENGLISH ARTISTIC DISCOURSE PRAGMASTILISTIC CHANGE AND THE MAIN RULES (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In the process of translating realities, the translator is required to have theoretical knowledge of national wide translation studies, as well as knowledge of the living conditions, culture, and customs of other nations. In general, the translation of a work of art depends on the personality of the translator, his and hers, and the translation process and the style of the text. realities, origins and differences between them are highlighted.